Studies on Aminobenzothiazole and Derivatives: Part-1. Synthesis of Intermediates –1,3-Di(substituted-phenyl)-thiourea using Ammonium Thiocyanate: Studies on Aminobenzothiazole and Derivatives: Part-1. Synthesis of Intermediates –1,3-Di(substituted-phenyl)-thiourea using Ammonium Thiocyanate - Patil, C. J. (International Journal of Pharmaceutical & Biological Archive, 2019)
1,3-Di(substituted-phenyl)-thiourea is used as intermediate in different reactions because they play an important role in synthesizing the different heterocyclic compounds. These reactions involve the synthesis of an intermediate, substituted-phenylammonium chloride which is converted to 1,3-Di(substituted-phenyl)-thiourea using ammonium thiocyanate. The final product formed, 1,3-Di(substituted-phenyl)-thiourea has potential to use as an intermediate in the synthesis of a building block for the heterocyclic compound, 2-aminobenzothiazole.